Pediatri yoğun bakım ünitesindeki entübe olan çocuk hastaların endotrakeal aspirasyon'a gösterdikleri ağrı davranışları ve ağrının değerlendirilmesi - TUNALI, İpek (My University, 2022)
This research was planned and carried out in order to measure and evaluate the pain behaviors of intubated pediatric patients hospitalized in the pediatric intensive care unit due to the endotracheal aspiration process and to determine the role of the nurse in controlling the pain that occurs. The universe of the research was composed of patients admitted to the Pediatric Intensive Care unit of Bezmialem Vakıf University Faculty of Medicine Hospital. All patients (60 patients) who were admitted to the Pediatric Intensive Care Unit and met the inclusion criteria of the study were included in the sample of the study. The data of this research, which determines the literature by the researcher obtained by the demographic characteristics of the patient and the patient taranila question 9 which consists of 7 questions that are evaluated during the treatment by 'Data evaluation form', FLACC Pain scale, the behavioral pain scale and the Wong-Baker face scale were collected using a. In the analysis of the data obtained from the study, the SPSS 24 program was used. Frequency and percentage analysis were used from descriptive analyses to evaluate the distribution of the study according to demographic characteristics. The mean and standard deviation were used to obtain descriptive analyses of the pain scales used in the study. An independent sample t-test was used to decipher the differences in the scores obtained from the pain scales according to the 2 groups, and a one-way anova analysis was performed to determine the differences between more than 2 groups. The study examined the demographic characteristics of the patients of pediatric patients in pediatric intensive care unit %36,7% girl %63.3% of male he is a child, %58,3% of complaints in addition to hospitalization, is a hereditary disease, %41,7% in the absence of another underlying disease, %60,0% is a medicine that is used during the normal life of, %40,0% if they were taking any medicine. Of the patients who underwent endotracheal intubation in the pediatric intensive care unit, 26.7% were diagnosed with respiratory distress, 13.3% were diagnosed with epilepsy, and 60% had other (heart disease, diabetic ketoacidosis, trauma, etc.) it has been determined that the diagnosis lies with the. It was found that pediatric patients included in the study expressed pain in different ways depending on the application of endotracheal aspiration. Looking at the way child patients describe pain; It was found that 17.0% vomited, 22.6% squeezed their eyes, 11.9% cried, 20.0% had a tense body posture, 19.6% grimaced, and 8.9% expressed it in other ways. Endotracheal suctioning of intubated pediatric patients on mechanical ventilation in the Pediatric Intensive Care Unit support related to changes in vital signs pediatric patients prior to aspiration of the process when looking at heart rate levels (X =113,18) aspiration after the procedure, the level of the heart while (X =120,12) is aspiration from the application of the pre-oxygen saturation levels (X =96,68) aspiration after the process of oxygen saturation level (X =96,32) it is revealed that. It was found that there was a positive increase between the results obtained from the pain scales used to measure and evaluate the pain levels of children with endotracheal aspiration prior to the aspiration procedure dec the results obtained from the evaluation after the procedure. Pediatric patients sedated and intubated in the Pediatric Intensive Care Unit followed flacc pain scale used in the evaluation of the level of pain measured Behavioral pain scale and Wong-Baker face scale their relationship with each other when looking at the process in line with the results obtained before and after endotracheal suctioning, it was determined that there is a correlation between low positive pain scales.
Yapılan bu araştırma pediatri yoğun bakım ünitesinde yatan entübe çocuk hastaların endotrakeal aspirasyon işlemine bağlı olarak gösterdikleri ağrı davranışlarınınin ölçülüp, değerlendirilmesi ve oluşan ağrının kontrol altına alınmasında hemşirenin rolünü belirlemek amacıyla planlanıp uygulanmıştır. Araştırmanın evrenini, Bezmialem Vakıf Üniversitesi Tıp Fakültesi Hastanesi Pediatri Yoğun Bakım ünitesine yatışı yapılan hastalar oluşturdu. Çalışmanın örneklemine ise Pediatri Yoğun Bakım Ünitesine kabul edilen ve araştırmanın dahil edilme kriterlerine uyan tüm hastalar (60 hasta) dahil edildi. Araştırmanın verileri araştırmacı tarafından literatür taranılarak elde edilen hastanın demografik özelliklerinin belirlendiği 9 soru ve hastanın takip tedavi süresince değerlendirilen 7 sorudan oluşan 'Veri Değerlendirme Formu', FLACC Ağrı Skalası, Davranışsal Ağrı Ölçeği ve Wong Baker Yüz Skalası kullanılarak toplandı. Araştırmanın elde edilen verilerin analizinde SPSS 24 programı kullanılmıştır. Araştırmanın demografik özelliklerine göre dağılımının değerlendirilmesinde betimleyici analizlerden frekans ve yüzde analizi kullanılmıştır. Araştırmada kullanılan ağrı ölçeklerinin betimleyici analizlerinin elde edilmesine ise ortalama ve standart sapmadan yararlanılmıştır. Ağrı ölçeklerinden elde edilen puanların 2' li gruplara göre farklılığının incelenmesinde bağımsız örneklem t- testi, 2' den fazla gruplar arasındaki farkların belirlenmesinde ise tek yönlü anova analizi yapılmıştır. Araştırmaya katılan pediatri yoğun bakımda yatan hastaların demografik özelikleri incelendiğinde çocuk hastaların %36,7'sinin kız çocuk, %63,3'ünün erkek çocuk olduğu, %58,3'ünün yatış şikayetlerine ek olarak kalıtsal hastalığı olduğu, %41,7'sinin altta yatan başka bir hastalığının olmadığı, %60,0'ının normal yaşamları süresince kullandığı bir ilacın olduğu, %40,0'ının ise hiçbir ilaç kullanmadığı saptanmıştır. Pediatri yoğun bakım ünitesinde endotrakeal entübasyon işlemi uygulanan hastaların %26,7' sinin solunum sıkıntısı tanısıyla, %13,3'ünün epilepsi tanısıyla, %60'ının ise diğer (kalp hastalığı, diyabetik ketoasidoz, travma vb.) tanılar ile yattığı saptanmıştır. Araştırmaya dahil olan çocuk hastaların endotrakeal aspirasyon uygulamasına bağlı olarak ağrıyı farklı şekillerde ifade ettikleri saptanmıltır. Çocuk hastaların ağrıyı ifade etme şekillerine bakıldığında; %17,0'sininde öğürme , %22,6'sında göz sıkma, %11,9'unda ağlama, %20,0'sinde gergin vücut postürü, %19,6'sinde surat buruşturma, %8,9'unda ise diğer ifadeler saptanmıştır. Pediatri yoğun bakım ünitesindeki mekanik ventilasyon desteği alan entübe çocuk hastaların endotrakeal aspirasyona bağlı olarak yaşamsal bulgularında meydana gelen değişikliklere bakıldığında çocuk hastaların aspirasyon işlemi öncesindeki Kalp atım düzeyleri (X ̅=113,18) iken aspirasyon işlemi sonrasındaki Kalp atım düzeylerinin (X ̅=120,12) olduğu, aspirasyon uygulamadan öncesindeki oksijen satürasyonu düzeylerinin (X ̅=96,68), aspirasyon işlemi sonrası oksijen satürasyon düzeyinin (X ̅=96,32) olduğu saptanmıştır. Endotrakeal aspirasyon işlemi uygulanan çocuk hastaların aspirasyon işlemi öncesinde ağrı düzeylerinin ölçülüp değerlendirilmesinde kullanılan ağrı ölçeklerinden elde edilen sonuçlar ile işlem sonrasında değerlendirmeden elde edilen sonuçlar arasında pozitif yönde bir artış olduğu saptanmıştır. Pediatri yoğun bakım ünitesinde entübe ve sedatize takip edilen çocuk hastaların ağrı düzeylerinin ölçülüp değerlendirilmesinde kullanılan FLACC Ağrı Skalası, Davranışsal Ağrı Ölçeği ve Wong Baker yüz skalasının birbirleri ile olan ilişkilerine bakıldığında endotrakeal aspirasyon işlemi öncesinde ve sonrasında elde edilen sonuçlar doğrultusunda ağrı ölçekleri arasında pozitif yönde düşük seviyede bir ilişki olduğu belirlendi.
Keywords: Pediatri yoğun bakım; entübasyon; endotrakeal aspirasyon; ağrı ölçekleri; hemşire; Pediatric intensive care unit; intubation; endotracheal aspiration; pain scales; nurse